Aplikasi Multimedia Pembelajaran untuk Mata Pelajaran Tematik Kelas 3 di SDIT Al-Kautsar Cikarang - Fajar Ridho Ardiansyah; Nuraini Purwandari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Learning materials play a crucial role in facilitating the learning process. However, at SDIT Al-Kautsar, Cikarang has not yet implemented learning media technology that can increase student engagement with the learning process. Consequently, the purpose of this study is to develop an interactive learning multimedia application for Class III Thematic subjects at SDIT Al-Kautsar Cikarang. Multimedia application development utilizes the Multimedia Development Life Cycle (MDLC), which consists of six stages: Concept, Design, Material Collection, Assembly, Testing, and Distribution. Interactive multimedia learning applications developed with Adobe Flash Professional CS6 and ActionScript 3.0. The advantage of this research is the creation of a multimedia interactive learning tool that can be utilized in the thematic learning process for third grade at SDIT Al-Kautsar, Cikarang. This application for interactive multimedia thematic learning has been tested using Black Box Testing and has received positive results.